2010
DOI: 10.1038/labinvest.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of orally administrated liposomal bovine lactoferrin on the LPS-induced osteoclastogenesis

Abstract: Bovine lactoferrin (bLF) modulates the production of proinflammatory cytokines including tumor necrosis factor (TNF)-a, and may thus control alveolar bone destruction associated with periodontitis. In this study, the effects of bLF on mRNA expression in lipopolysaccharide (LPS)-stimulated osteoblasts (OBs) and on LPS-induced osteoclastogenesis were examined. The inhibitory effects of oral administration of liposomal-bLF (L-bLF), which improved the robustness of bLF to digestive enzymes, on alveolar bone resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 41 publications
5
43
0
Order By: Relevance
“…The results of RT-PCR and immunohistochemical analysis indicated that bovine lactoferrin treatment not only increased the expression level of OPG but also slightly decreased the expression level of RANKL in the distraction gap, leading to a significantly lower RANKL/OPG ratio in the distracted calluses compared with the untreated distraction osteogenesis group. Our results agree with those of previous studies [11,35] indicating that the OPG/RANKL/RANK system might be a major mechanism for increased bone formation and decreased bone resorption in distraction osteogenesis using bovine lactoferrin treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The results of RT-PCR and immunohistochemical analysis indicated that bovine lactoferrin treatment not only increased the expression level of OPG but also slightly decreased the expression level of RANKL in the distraction gap, leading to a significantly lower RANKL/OPG ratio in the distracted calluses compared with the untreated distraction osteogenesis group. Our results agree with those of previous studies [11,35] indicating that the OPG/RANKL/RANK system might be a major mechanism for increased bone formation and decreased bone resorption in distraction osteogenesis using bovine lactoferrin treatment.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study we demonstrated that oral administration of liposomal bLF, which exhibits improved stability in the stomach and enhanced absorption by the intestinal tract, significantly reduces alveolar bone resorption by decreasing TNF-␣ production by host cells stimulated with LPS (3). In addition, our in vitro analysis showed that bLF pretreatment inhibits LPS-induced TNF-␣ and RANKL (receptor activator of nuclear factor B ligand) expression in ST2 cells (a bone marrow-derived osteogenic cell line).…”
Section: Lactoferrin (Lf)mentioning
confidence: 99%
“…We have already demonstrated that many positive cells to a bLF antibody were immunohistochemically detected in periodontal tissue of LbLF-fed rats, 20) which suggests that bLF or its fragment absorbed from the intestine might show anti-inflammatory effects in this study, although further study is needed to elucidate the biological mechanism of L-bLF. On the other hand, we have already reported that soy phosphatidylcholine itself inhibited TLR4-mediated MCP-1 expression in vascular cells.…”
Section: Discussionmentioning
confidence: 63%
“…Our previous studies have shown that the oral administration of liposomal bLF (L-bLF) exhibited more suppressive effects than non-liposomal bLF on LPS-induced TNF-a production from mouse PBMCs, 19) as well as on osteoclast increase or TNF-a expression in marginal periodontal tissue of a rat LPS-induced periodontitis model. 20) In the present study, LbLF was orally administered to subjects with periodontal disease to investigate whether it can be useful for treating periodontal disease. …”
mentioning
confidence: 99%